2009
DOI: 10.1210/jc.2009-0766
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Body Fat Mass and Inflammatory Marker Increases after Long-Term Cure of Cushing’s Syndrome

Abstract: Despite long-term cure, patients who have suffered CS exhibit persistent accumulation of central fat, as in active hypercortisolemia, with the consequent unfavorable adipokine profile, leading to a state of low-grade inflammation. This situation determines a persistent and increased cardiovascular risk in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
128
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(143 citation statements)
references
References 29 publications
13
128
2
Order By: Relevance
“…Adipose tissue mass decreases after treatment for CS (4,7,8,9,10), but whether complete normalisation occurs at long-term follow-up is not fully explored. One previous cross-sectional study found an increased total and abdominal fat mass in patients with CS after a mean time of 11 years in remission in comparison with age-, gender-and BMI-matched controls (11). Our results also indicate that the central obesity associated with long-term hypercortisolism in CS is not completely reversible after treatment.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Adipose tissue mass decreases after treatment for CS (4,7,8,9,10), but whether complete normalisation occurs at long-term follow-up is not fully explored. One previous cross-sectional study found an increased total and abdominal fat mass in patients with CS after a mean time of 11 years in remission in comparison with age-, gender-and BMI-matched controls (11). Our results also indicate that the central obesity associated with long-term hypercortisolism in CS is not completely reversible after treatment.…”
Section: Discussionsupporting
confidence: 62%
“…Our results also indicate that the central obesity associated with long-term hypercortisolism in CS is not completely reversible after treatment. Previous studies on the reversibility of reduced LBM and skeletal muscle mass have demonstrated either unchanged (4,8,9,10) or reduced LBM after treatment (7,11). In our study, after adjustment for various confounders, no difference in skeletal muscle mass was observed between patients and controls.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…This might be attributable to the persistence of hypercortisolemia for parts of each day, and to persistently higher visceral fat mass after the treatment. In human studies, subjects with Cushing's syndrome have persistent central fat mass, higher leptin concentrations, and other abnormal adipokines, even after long‐term cure 35, 36. Therefore, it is possible that the maintenance of hyperleptinemia might have been the result of secretion of leptin by the persistent central fat mass in dogs with PDH.…”
Section: Discussionmentioning
confidence: 99%
“…Both hypertension and central obesity are more prevalent in active CS patients than in remission, and they tend to persist for long term, for a mean of eleven years (37). Elevated total trunk fat mass and low lean body mass are characteristics of active CS.…”
Section: Metabolic Syndromementioning
confidence: 99%